Restriction Endonuclease Analysis of Herpes Simplex Virus from Recrudescent Lesions, from Latent Infection and During Passage in the Skin and Nervous System of Mice - Darville, J. M.; Harbour, D. A.; Hill, T. J.; Blyth, W. A. (Journal of General Virology, 1987)
SUMMARY The stability of the restriction endonuclease profile of herpes simplex virus type 1 strain SC 16 in mice was studied. Virus isolated from skin during acute infection was compared with that from latently infected ganglia and with that from recrudescent lesions induced by trauma. In another experiment virus serially passaged only in skin was compared with virus that had also replicated in the nervous system. The loss or gain of specific restriction sites was not observed but in some cases the mobility of certain fragments decreased.
Keywords: skin